Restoring the brain : neurofeedback as an integrative approach to health - Kirk, Hanno W. (New York, NY : Routledge, 2020)
"This thoroughly updated second edition of Restoring the Brain is the definitive book on the theory and the practice of Infra-Low Frequency brain training. It provides a comprehensive look at the process of neurofeedback within the emerging field of neuromodulation and essential knowledge of functional neuroanatomy and neural dynamics to successfully restore brain function. Integrating the latest research, this thoroughly revised edition focuses on current innovations in mechanisms-based training that are scalable and can be deployed at any stage of human development. Included in this edition are new chapters on clinical data and case studies for new applications; using neurofeedback for early childhood developmental disorders; integrating neurofeedback with psychotherapy; the impact of low-frequency neurofeedback on depression; the issue of trauma from war or abuse; and physical damage to the brain. Practitioners and researchers in psychiatry, medicine, and behavioral health will gain a wealth of knowledge and tools for effectively using neurofeedback to recover and enhance the functional competence of the brain"--
7.2 Case Study #1: Bipolar I Disorder, Postpartum Mixed Episode -- 7.3 Case Study #2: Severe Generalized Anxiety Disorder with Severe Alcohol Use Disorder -- 7.4 Conclusion -- Notes -- 8. Remediating Brain Instabilities in a Neurology Practice -- 8.1 Introduction -- 8.2 Case Vignettes -- 8.3 Exploiting Neuroplasticity -- 8.4 Patient Selection -- 8.5 Prescribing Brain Training Protocols -- 8.6 Viewpoints: Neurofeedback Practice in a Neurology Office -- 8.7 Summary Statement -- Notes -- Part III: Specific Applications Areas of Neurofeedback
OCLC-licensed vendor bibliographic record.
Keywords: Neurofeedback; Brain -- Physiology; Mental illness -- Treatment; MEDICAL / Psychiatry / General; MEDICAL / Neuroscience; PSYCHOLOGY / Neuropsychology